A Study to Assess the Effectiveness of Information Booklet on Knowledge and Attitude Toward Controlling Blood Pressure Among Clients with Hypertension in Medical College Hospital, Jabalpur - Rashmi Sahu (Indian Journal of Nursing Sciences, 2024)
Aim: The purpose of this study was to evaluate how well an information booklet at Medical College Hospital in Jabalpur improved the knowledge and attitudes of hypertension patients about blood pressure control. Introduction: Hypertension is a prevalent and serious health condition that contributes to a significant number of cardiovascular diseases worldwide. Effective management of hypertension requires patient education to improve self-care practices and medication adherence. The objective of this study was to evaluate the impact of an information booklet on hypertensive patients’ knowledge and attitudes. Materials and Methods: A pre-experimental design was adopted for this study, involving 100 participants diagnosed with hypertension from Medical College Hospital, Jabalpur. Convenience sampling was used to select the participants. An information booklet focusing on hypertension, its causes, risk factors, preventive measures, and treatment options was provided to the participants. Pre-test and post-test assessments were conducted using structured questionnaires to evaluate the changes in participants’ knowledge and attitudes regarding hypertension management. Results: The findings demonstrated a significant increase in both knowledge and attitude scores after the intervention. The mean knowledge score improved from 12.5 ± 3.2 to 22.6 ± 4.1, whereas the mean attitude score increased from 18.7 ± 2.9 to 28.4 ± 3.6 (P < 0.05). These results suggest that the booklet effectively enhanced understanding and fostered positive attitudes toward hypertension management. Conclusion: The information booklet effectively improved the knowledge and attitudes of hypertensive patients, underscoring the importance of educational interventions in managing hypertension.